Home phototherapy in vitiligo - Tasneem F. Mohammad (2018)
© 2017 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd Vitiligo is a disorder characterized by the development of depigmented macules and patches. Narrowband ultraviolet B phototherapy is a standard of care treatment and is used both as monotherapy and in combination with other treatment modalities to induce repigmentation. Although phototherapy is safe and effective, its use is limited due to the significant time commitment required and associated costs. Home phototherapy is a safe and effective alternative to make phototherapy more accessible to patients. However, it is often underutilized due to lack of physician experience and comfort as well as misconceptions regarding its safety and efficacy. This article provides a brief overview of the use of phototherapy in vitiligo with a focus on home phototherapy in order to increase awareness and use of this treatment modality.